PERENCANAAN INSTALASI PENGOLAHAN AIR LIMBAH DOMESTIK (IPALD) SKALA KOMUNAL DESA SUKOHARJO KECAMATAN MARGOREJO KABUPATEN PATI - Antoni, Ahmad; Bintara, Aditya Surya; Rizani, Mohammad Debby; Yudaningrum, Farida (Jurnal Teknik Sipil Giratory UPGRIS, 2022)
AbstractDomestic wastewater in Sukoharjo Village, Margorejo District, Pati Regency hasn’t been managed optimally, even there’s already a Domestic Wastewater Treatment Plant (DWWTP) build, but it’s only intended for 46 SR. Based on these conditions, a DWWTP with a capacity up to 200 SR will be planned so that it can cover more residents. The DWWTP planning begins with licensing, field surveys, data collection, literature study, planning, discussion, and conclusions. Primary data that used is field observations, COD and BOD data, then secondary data that used is Population Data, Groundwater Level, Land Slope, STBM, and Gambiran DWWTP Working Drawings. This DWWTP planning uses combination of ABR and AF wastewater treatment techniques. The use of clean water for 200 SR is 90 m/day, with a waste volume of 72 m/day and a sludge volume of 15 m/year. The wastewater has 15 mg/L BOD values and 40 mg/L COD Values. Based on the planning results, the DWWTP design was obtained which includes 1 inlet tank measuring 1 x 1 m with a depth of 3 m, 1 settler tank 3.5 x 3.5 meters with a depth of 3.5 m, 4 ABR tanks 1 x 3.5 m with a depth of 3.5 m, as well as 4 1 x 3 m AF tanks with a depth of 3.5 m. 6-inch diameter PVC pipe used to drain the waste water, accompanied by 85 control tubs with a diameter of 0.6 meters.Keywords: Domestic Wastewater Treatment Plant, Anaerobic Baffled Reactor, Anaerobic Filter, Domestic Wastewater